2003
DOI: 10.3354/meps253111
|View full text |Cite
|
Sign up to set email alerts
|

Current patterns, habitat discontinuities and population genetic structure: the case of the kelp Laminaria digitata in the English Channel

Abstract: Laminaria digitata is the dominant species of the dense, continuous kelp stands in the English Channel and on the Atlantic coasts of France, where it is harvested for its high quality alginates. However, in spite of its ecological and economic importance, our knowledge of the level and organisation of genetic diversity in this species is scant. Here, using comprehensive hierarchical sampling and 7 microsatellite loci, we explored the roles of dispersal strategies, current regimes and habitat discontinuities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
128
4
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(157 citation statements)
references
References 60 publications
17
128
4
8
Order By: Relevance
“…Admittedly, Bolton & Lüning (1982) did not find ecotypic differentiations in thermal responses within gametophytes of S. latissima isolates from France, Brittany, Norway, or HLG or from L. digitata isolates from Canada and HLG. But investigations by Billot et al (2003) found genetic differentiations in continuous, nonfragmented forests of L. digitata at distances greater than only 10 km. The different capacities for sporophyte formation of S. latissima demonstrated here through crossing experiments between Arctic and HLG isolates support additionally an ecotypic differentiation in S. latissima (Fig.…”
Section: Thermal Ecotypes In Laminariales From Arctic and Cold-tempermentioning
confidence: 99%
“…Admittedly, Bolton & Lüning (1982) did not find ecotypic differentiations in thermal responses within gametophytes of S. latissima isolates from France, Brittany, Norway, or HLG or from L. digitata isolates from Canada and HLG. But investigations by Billot et al (2003) found genetic differentiations in continuous, nonfragmented forests of L. digitata at distances greater than only 10 km. The different capacities for sporophyte formation of S. latissima demonstrated here through crossing experiments between Arctic and HLG isolates support additionally an ecotypic differentiation in S. latissima (Fig.…”
Section: Thermal Ecotypes In Laminariales From Arctic and Cold-tempermentioning
confidence: 99%
“…Fortunately, when sharp clines occur in species with sedentary adults, it facilitates experimental methods that can distinguish between patterns produced by dispersal barriers versus postdispersal selection (Koehn et al 1980;Bierne et al 2003;Gilg and Hilbish 2003;Toro et al 2004). Also, directional gene flow has been detected in several marine systems (Wares et al 2001;Billot et al 2003) and estimates should improve through the use of high-resolution genetic markers (Estoup et al 1999;Mountain et al 2002) and analyses designed to take advantage of them (Falush et al 2003;Wilson and Rannala 2003;Hey et al 2004). Thus, the experimental tools exist to test for patterns of nonrandom gene flow that could accentuate differentiation within a species.…”
Section: Implications and Prospects For Further Analysismentioning
confidence: 99%
“…Essa flutuação randômica da frequência dos genes é denominada de deriva genética . O fluxo gênico é o processo migratório de alelos que ocorre preferencialmente entre populações adjacentes (Billot et al, 2003). Entretanto, a descontinuidade de habitats, tais como a presença de desembocaduras de rios e trechos de substrato impróprio, entre outros, pode criar barreiras para o fluxo gênico e favorecer a diferenciação genética (Kimura & Weiss, 1964;Faugeron et al, 2001;Billot et al, 2003).…”
Section: Diversidade Intraespecíficaunclassified
“…O fluxo gênico é o processo migratório de alelos que ocorre preferencialmente entre populações adjacentes (Billot et al, 2003). Entretanto, a descontinuidade de habitats, tais como a presença de desembocaduras de rios e trechos de substrato impróprio, entre outros, pode criar barreiras para o fluxo gênico e favorecer a diferenciação genética (Kimura & Weiss, 1964;Faugeron et al, 2001;Billot et al, 2003). Estudos indicam que para as algas a diferenciação genética pode ocorrer a partir de distâncias relativamente curtas, maiores que um metro e menores que 10 km (Billot et al, 2003).…”
Section: Diversidade Intraespecíficaunclassified
See 1 more Smart Citation